Inovasi Pengelolaan Dana Sosial Keagamaan melalui Aplikasi Mobile ZIS: Studi Kasus Masjid Raya An-Nur: Innovation in Managing Religious Social Funds through a Mobile ZIS Application: A Case Study at Masjid Raya An-Nur - Rozi, Imam Fahrur; Yunianto, Dika Rizky; Yunhasnawa, Yoppy; Purnomo, Fadjar; Amalia, Astrifidha Rahma; Arifin, Muh. Syamsul; Sholeh, Moch.; Viyus, Vinan; Hakim, Muhammad Ilham El (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The management of zakat, infaq, and sadaqah (ZIS) funds in many mosques is still carried out conventionally, leading to inefficiencies in collection, reporting, and distribution, as well as limited transparency and accountability. Masjid Raya An-Nur at Politeknik Negeri Malang, as a religious activity center, plays a strategic role in managing community funds. However, its manual system has hindered timely financial recording and reporting. The main challenges include limited access for donors to contribute online, slow verification processes, and a lack of transparency that may reduce public trust. To address these issues, this community service program developed and implemented an Android-based mobile application for ZIS management. The methodology involved a needs analysis through interviews and observations, system design utilizing REST API architecture with a Laravel back-end and MySQL database, and user training for both administrators and donors. The results indicate that the application successfully facilitates online donations, provides real-time reporting, and enhances donor participation through transparency features and digital reminders. Furthermore, the payment gateway integration enables more flexible and secure payment methods. Overall, the system has improved the efficiency, transparency, and accountability of ZIS management at Masjid Raya An-Nur, strengthened donor trust, and contributed to the digital transformation of religious social fund governance.